(untitled) (Salud, Arte y Cuidado, 2023)
The objective of this study is to determine the clinical and epidemiological characteristics of the patient with a central venous catheter, hospitalized in the Intensive Care Unit Decentralized Service Hospital Universitario Pediatric Dr. Agustín Zubillaga, Barquisimeto, Lara State. Regarding the research methodology, it has a quantitative approach, descriptive type of field design, non-experimental, cross-sectional, the population was 11 patients from the Intensive Care Unit. The instrument was applied to this population, with the prior informed consent of the parents, obtaining as results that epidemiologically the female sex is the most frequent as well as the age between 29 days to 2 years of age and a nutritional status classified using the z score in 0. On the other hand, the clinical characteristics found that the most frequent stay time was 4 days, the mechanical complication was the local hematoma, in addition, no infectious complications related to the central venous catheter were linked, the blood culture was mostly negative only two patients had a positive blood culture, the most frequent indication was the use of amines and all the patients who were admitted to the intensive care unit carried a central venous catheter, the most commonly used size is 5-20 cm with 3 lumens , made of polyurethane, the most frequent type of access is the jugular and the placement success was one attempt as well as t also the amount of catheter used. Keywords: clinical characteristics, central venous cathete, epidemiology